VD_FINDINFO HC / 2014 / 587 vom 28. Juli 2014 - VD Tribunal cantonal (2014)
CAS CLAIR, PROCÉDURE SOMMAIRE, EXPULSION DE LOCATAIRE, SOMMATION, BAIL À LOYER | 257d al. 1 CO, 257d CO, 257 al. 1 CPC (CH), 257 CPC (CH)